An information system on genomic elements and predicted protein structures of buffalo (Bubalus bubalis) - KAIRI, AMIT; SAHU, TANMAYA KUMAR; RAO, ATMAKURI RAMAKRISHNA (The Indian Journal of Animal Sciences, 2021)
Among the livestock species, buffalo remained as an integral part of the Indian rural economy. With the advent of genome sequencing technologies, it became possible to sequence the whole genome of Murrah buffalo. Also, significant amount of information on different genomic elements of buffalo is available at National Centre for Biotechnology Information (NCBI). However, the positions of these elements on the genome are not fully known. In addition, the 3D structures of buffalo proteins are not available and also there exist no browser to visualize important genic elements on buffalo genome. Hence, a study was taken up to develop a web-based information system having information on genomic elements, protein 3-D structures and genome browser. Initially, information on nucleotide and protein sequences were retrieved from NCBI and parsed suitably. Later, the protein structures were predicted, validated, refined and stabilized in silico. An Information System on Buffalo Genome (ISBG) with 3-tier architecture was developed containing the sequence and structural information. ISBG contains complete coding sequences (CDS), Mitochondrial DNAs, 1k upstream regions and Untranslated Regions (UTRs) of buffalo genome. The buffalo genes were also mapped onto the genome. The results revealed that maximum number of genes were found distributed on chromosome 4 followed by chromosome 18, which can also be visualized from the developed genome browser. ISBG can be accessed at http://cabgrid.res.in:8080/bgis. The proposed information system helps animal breeders and biotechnologist in animal improvement.